Assessing manifestations of bossing in the context of personality traits of business managers - Stefko, Robert; Birknerova, Zuzana; Zbihlejova, Lucia; Nebesky, Lubomir (Frontiers in Psychology, 2023)
Introduction Abusive supervision or bossing represents a specific form of mobbing as a long-term, systematic negative action by superiors toward subordinates. Methods From the point of view of the operationalization of this construct, the original BOSSm18 methodology is presented in the paper in the context of the B5 methodology, which enables specification of personality traits in terms of the original Big Five concept. Results Based on the research dataset of 636 business managers, the paper presents the results of the basic psychometric parameters of the methodology and the content specification of the extracted factors. The research findings support a multidimensional understanding of the bossing construct. Discussion The limiting factors of the interpretation and generalization of the results relate to the consideration of cultural contexts and situational conditions of perception of bossing manifestations.